Development and validation of recombinant proteins for defence mechanism induction against papaya dieback disease caused by Erwinia mallotivora - Bakar, Ros Azrinawati Hana (2022)
Erwinia mallotivora (EM) is a Gram-negative bacterium causing dieback disease of papaya. This disease affects the whole part of the plant, initially changing the colour of the leaves and subsequently leading to wilting and death of the infected plants. Synthetic pesticides and cultural practices are among the strategies utilised to control the disease in the field. The adoption of effector proteins in promoting plant defence mechanisms by inducing specific defence mechanisms responses has been reported to be a promising control method. This study used harpin protein as the main ingredient in developing the bio-bactericide. Previous studies showed that harpin proteins could induce systemic acquired resistance (SAR) in plants and eventually increase the host resistance against bacterial infections. The plasmid DNA extraction was conducted using the GeneJET Plasmid Miniprep Kit (Thermo Scientific, USA), according to the manufacturer’s recommendations. Two selected harpin proteins i.e. Hrp I and Hrp II, were used in this study to control the disease in glasshouse and field trials. The first objective was to transform, express, and purify Hrp I and II as SAR inducers in a bacterial system, Escherichia coli. The results showed that Hrp I and II were successfully transformed, expressed, and purified, with an estimated proteins size of ~30 and ~ 45 kDa. The second objective was to assess the effectiveness of Hrp I and II as the SAR inducers at the glasshouse trial. The results of the foliar application revealed the protection index were 70.8% and 35.7% of Hrp I and Hrp II, respectively. The third objective was to assess the potential and effectiveness of Hrp I as a SAR inducer in the field trial. The field trial results demonstrated that a promising protection index of 72.3%. Furthermore, the plant growth promotion attributes were also observed in the treated plants. Finally, the fourth objective was to validate the selected defence-related genes by gene expression on the treated and untreated plants via RT-qPCR analysis. The results indicated that the papaya plants treated with Hrp I possess the highest expression of gene-related defence like PRX, OSM, and PR-ID both in the glasshouse and field trials. In conclusion, the adoption of the Hrp I is a promissing disease control approach in managing papaya dieback disease under both glasshouse and field conditions